Fibroblast Upregulation of Vitamin D Receptor Represents a Self-Protective Response to Limit Fibroblast Proliferation and Activation during Pulmonary Fibrosis - Juan Wei; Junhui Zhan; Hui Ji; Yitong Xu; Qingfeng Xu; Xiaoyan Zhu; Yujian Liu (Antioxidants, 2023)
Dysregulation of vitamin D receptor (VDR) is implicated in chronic obstructive pulmonary disease. However, whether VDR dysregulation contributes to the development of pulmonary fibrosis remains largely unknown. Analysis of bulk and single-cell RNA profiling datasets revealed VDR upregulation in lung fibroblasts from patients with pulmonary fibrosis or fibrotic mice, which was validated in lung fibroblasts from bleomycin-exposed mice and bleomycin-treated fibroblasts. Stable VDR knockdown promoted, whereas the VDR agonist paricalcitol suppressed lung fibroblast proliferation and activation. Gene set enrichment analysis (GSEA) showed that the JAK/STAT pathway and unfolded protein response (UPR), a process related to endoplasmic reticulum (ER) stress, were enriched in lung fibroblasts of fibrotic lungs. Stable VDR knockdown stimulated, but paricalcitol suppressed ER stress and JAK1/STAT3 activation in lung fibroblasts. The STAT3 inhibitor blocked bleomycin- or stable VDR knockdown-induced ER stress. Paricalcitol inhibited the bleomycin-induced enrichment of STAT3 to the ATF6 promoter, thereby suppressing ATF6 expression in fibroblasts. Paricalcitol or intrapulmonary VDR overexpression inactivated JAK1/STAT3 and suppressed ER stress in bleomycin-treated mice, thus resulting in the inhibition of fibroblast proliferation and activation. Collectively, this study suggests that fibroblast VDR upregulation may be a self-protective response to limit fibroblast proliferation and activation during pulmonary fibrosis by suppressing the JAK1/STAT3/ER stress pathway.